Staff Development Initiatives' Effect on Teaching Faculty Performance in Taraba State Higher Education Institutions - Joseph Tanimu; Andesimbapae Sam Wachap; Friday Tanko (Sciental Journals Publishing, 2024)
The paper examines how staff development programs affect the performance of teaching faculty at higher education institutions in Taraba State, Nigeria. A mixed-methods approach was utilized to collect data, with a focus on respondents' perceptions of staff development programs and their influence on teaching faculty performance. The research sample consisted of 200 persons, including school administrators and instructional personnel. Descriptive statistical analyses were performed to calculate the mean scores and standard deviations of Likert-scale responses to various aspects of staff development programs. Furthermore, hypotheses were tested to determine whether there were any significant relationships between respondents' opinions about staff development activities and teaching faculty performance. According to the survey results, respondents feel that staff development programs improve teaching faculty effectiveness, nurture workplace performance, encourage teacher innovation, and increase job satisfaction. Despite widespread agreement, response variability suggests that people have a diversity of perspectives. Furthermore, the findings indicate a significant relationship between school administration and teaching faculty opinions of the effectiveness of staff development initiatives, emphasizing the need of collaboration and stakeholder participation in educational reform efforts. Based on these findings, recommendations are made to tailor staff development programs to the specific needs of teaching faculty, conduct on-going needs assessments, promote collaboration and peer learning, allocate adequate resources and support, advocate for supportive policies, and conduct rigorous research and evaluation. These aim to improve teaching staff performance, therefore adding to the quality of higher education in Taraba State, Nigeria.
Keywords: Staff Development; Teaching Faculty; Higher Institutions; Performance